Aspek kegunaan dan kemudahan pada penggunaan aplikasi Candil (Maca Dina Digital Library) - Devi Rizkyana; Elnovani Lusiana; Encang Saepudin (Jurnal Informatio, 2021)
Candil is a digital library application that allows users to access library collections via cell phones, this application launched by Dinas Perpustakaan dan Kearsipan Daerah Provinsi Jawa Barat. With this application, users from various regions can access the library’s collections without any problems. It is important to analyze the extent to which this digital library application can be accepted by its users. Because by knowing how users respond to this digital library application, it can also be seen the advantages and disadvantages in it. This study aims to determines usefulness aspect and ease of use aspect of using the Candil application which can be used as a consideration in developing the digital library application. This research method uses a qualitative approach with case study analysis. The informants of this study were Candil application users and staff of Dinas Perpustakaan dan Kearsipan Daerah Provinsi Jawa Barat. The data collection techniques was carried out through observation, interviews, and documentations. Data analysis techniques are carried out through data collection, data reduction, data display, and verification. The results showed that the usefulness aspect was built on several items such as work more quickly, makes job easier, increase productivity, and useful. The items that have not been fulfilled in the usefulness aspect are job performance and effectiveness. The ease of use aspect was built on several items such as easy to use, controllable, easy of learn, easy to become skillful, and clear and understandable. The item that has not been fulfilled in the ease of use aspect is flexibility. The conclusion of this study shows that overall the Candil application is quite easy to use and provides benefits for its users even though there are some obstacles that can still be overcome. These obstacles are like applications that sometimes experience lag or difficulty connecting to the internet network, which users can still handle.